Simultaneous Determination of Sufentanil and Ziconotide in Combination for Intrathecal Analgesia by UPLC-UV - Sorrieul Jérémy; Gibory Vincent; Dinh Chau Phi; Kieffer Hélène; Folliard Caroline; Dupoiron Denis; Devys Catherine (De Gruyter, 2016)
Intrathecal analgesia has increased over the past two decades based on high level proof of efficacy in patients with cancer. Morphine and Ziconotide remains the reference. Polyanalgesic Consensus Conference IT treatment algorithm recommends as the second line therapy opioids/ziconotide combination. Sufentanil and ziconotide combination can be used. The implantable pumps development helped to improve the comfort of the patient. The refills were prepared under a laminar airflow hood under strictly aseptic conditions, by the hospital pharmacist. In order to secure the process, a new analytical method by simple liquid chromatography ultraviolet spectrometry method was developed for the simultaneous quantification of two analgesic drugs (sufentanil, ziconotide). The method was validated according to the recommendation of the US Food and Drug Administration (FDA). The method was linear between 0.1 to 4 μg/mL for ziconotide and 3.125 to 50 µg/mL for sufentanil. This routine quality control analysis secures the production process.